2020
DOI: 10.1177/1742395320968617
|View full text |Cite
|
Sign up to set email alerts
|

The information and support needs of patients living with inflammatory bowel disease: A qualitative study

Abstract: Objectives To explore patients’ experiences of living with inflammatory bowel disease (IBD) with a focus on their information and support needs. Methods Qualitative interview study involving adults diagnosed with IBD recruited through social media. Interviews were audio recorded, transcribed and data were analysed thematically. Results Interviews with 15 patients (9 females, 6 males) highlighted how misdiagnosis or hesitation to diagnose had caused frustration and anxiety. Once diagnosed, only a few participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Dietary information needs appear to be influenced by stages of IBD: pre-diagnosis, diagnosis, relapse and remission. 20,21,23,27,44,47,50,53,60,63,64,67,70 However, most studies report on the perceptions of the role of diet and food in IBD, and provide a description of lived experiences, rather than what dietary information is desired/ needed. 23,50,53,63,64,67 The dietary information needs at pre-diagnosis and remission were scarcely described in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary information needs appear to be influenced by stages of IBD: pre-diagnosis, diagnosis, relapse and remission. 20,21,23,27,44,47,50,53,60,63,64,67,70 However, most studies report on the perceptions of the role of diet and food in IBD, and provide a description of lived experiences, rather than what dietary information is desired/ needed. 23,50,53,63,64,67 The dietary information needs at pre-diagnosis and remission were scarcely described in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…19,21,47,50,53,55,63,64,66,67 Notably, only one of the included studies reported no differences in information seeking behaviour during relapse and remission. 22 Eleven studies 20,23,44,45,47,50,53,60,63,70 and the Crohn's and Colitis New Zealand survey 67 provided some detail as to the dietary information needs of individuals with IBD at diagnosis and relapse (Table 2). Topics of interest related to knowledge of specific foods or food components to avoid Remission is reported as % when available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a need in gastroenterology healthcare to improve the accuracy of the diagnosis of IBD and to distinguish UC and CD with a sensitive and cost-effective system. This may improve the patient's quality of life and provide endoscopists with medical devices for improving the accuracy and efficiency of diagnosis and treatment (17).…”
Section: Introductionmentioning
confidence: 99%
“… 22 Despite the importance of these information needs, people living with IBD report that access to information is lacking, especially for people experiencing vulnerability (eg, young people). 23 25 …”
Section: Introductionmentioning
confidence: 99%